PERAN KONSELOR SEKOLAH DALAM PENGEMBANGAN PENDIDIKAN KARAKTER MELALUI PELAYANAN BIMBINGAN KONSELING DI SEKOLAH - Meidy D. Ar Noya; Jenny M. Salamor (PSIKOLOGI KONSELING, 2020)
Character education was one of the focuses in the system of national education. Therefore, educators must not neglect this. A school counselor, as one of the educators, has to play a role in character education. Referring to guidance and counseling responsibilities in relation to students’ personal, social, academic, and career aspects, a school counselor must not escape from the main duties. Considering that character education is the responsibility of all parties, a school counselor can, independently and in collaboration with all school components, play a role in character education. Individually, a school counselor can provide services, such as individual services, individual planning services, and responsive services. In collaboration with other parties, a school counselor can make a synergy in character education programs. While guidance and counseling services are one of the service programs that contribute to the implementation of the program in schools. So that it is expected that the implementation of strengthening of character education through guidance and counseling services in schools can be implemented and implemented effectively and efficiently, so that it can achieve more optimal goals for the development of character values that exist in students.Keywords: School Counselors; Character Education; Counseling Guidance Services